Hierarchical Plans and Their Functions in Islamic Educational Organizations - Jumiati; M.Sirozi (al-Afkar, Journal For Islamic Studies, 2025)
This study aims to analyze hierarchical plans and their functions in Islamic educational organizations to ensure the direction and operational success. The research method used is qualitative with a library research approach. The data collection technique is a method of understanding and learning about the stories from various types of literature that are related to the publication of books, journals and reports that have been carried out.Hasil penelitian menunjukan bahwa Hierarchical Plans or Hierarchical Planning is a planning system that focuses on the preparation and arrangement of organizational structures in stages or tiers. Hierarchical planning in Islamic educational organizations requires a systematic and planned approach. By setting clear goals, building an effective organizational structure, and conducting regular supervision and evaluation, schools can achieve educational goals optimally. Hierarchical planning in Islamic educational organizations has many important functions, ranging from the preparation of a clear division of tasks to the improvement of efficiency, coordination, communication, and supervision. The primary function of hierarchical planning is to create a clear and efficient structure that allows educational organizations to operate smoothly and effectively.